Hugh MacDiarmid’s Poetics of Commitment: the Modern Stigmata of Bereavement - Béatrice DUCHATEAU (E-REA)
In the 1930s, the lingering absence of God and of a stable reality engulfed the work of the poet Hugh MacDiarmid, leader of the Scottish Renaissance Movement. To counter this void, like many others at the time, MacDiarmid found refuge in communism and nationalism and started to write political and idealist poetry. In his poems, his political idealism comes into being in the association of reality and ideal, symbolised first by Jean and Sophia, the characters of A Drunk Man Looks at the Thistle (1926), and duplicated later in the fantasised image of Lenin, perfect blending of idea and action. Rejecting Sartre’s denial of the political effect poetry can have, the violence of MacDiarmid’s work desperately attempts to have reality submit to its aura. The shrill imperative and nominal forms of the poems borrow their power of persuasion from advertisement slogans while the poetic margins endeavour to mimic performative oracles. In the violence of the poetry and in Hugh MacDiarmid’s extreme political commitment, one can recognise the refusal to mourn the very concept of reality in a world born out of shrapnel seeds.